1985
DOI: 10.1007/bf01252612
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic kindling: What has it taught us about epilepsy?

Abstract: We reviewed recent evidence that chemical kindling of epileptic seizures can be induced by injection into the amygdala of multiple cholinergic muscarinic agonists, and blocked by multiple muscarinic antagonists. The stereospecific induction of kindling by (+) but not by (-) acetyl-beta-methylcholine shows that some types of repeated synaptic activation can produce epilepsy, in the absence of specific brain damage. The failure of bicuculline (but not of carbachol) to produce kindling with amygdaloid injections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Miller et al 1994;Ferencz et al 1998) have shown that theta rhythm has seizure-resistant effects in rats. Further, Burchfiel et al (1979) showed that the kindling model of epilepsy in rats is associated with hippocampal supersensitivity to acetylcholine and Wasterlain et al (1985) showed that cholinergic agonists in the rat amygdala can induce kindling, suggesting that the protective effects are due to aspects of the theta rhythm beyond simply the release of acetylcholine in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al 1994;Ferencz et al 1998) have shown that theta rhythm has seizure-resistant effects in rats. Further, Burchfiel et al (1979) showed that the kindling model of epilepsy in rats is associated with hippocampal supersensitivity to acetylcholine and Wasterlain et al (1985) showed that cholinergic agonists in the rat amygdala can induce kindling, suggesting that the protective effects are due to aspects of the theta rhythm beyond simply the release of acetylcholine in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that repeated application of CCh to the amygdala in subconvulsive doses induces a kindling process that can be prevented by atropine and pirenzepine, which suggests the involvement of M1 muscarinic receptors (Wasterlain and Jonec 1983; Wasterlain et al, 1985; Lupica and Berman, 1988). Application of a muscarinic receptor antagonist likewise affected the kindling rate, but had no effect on persistent seizures after animals had been fully kindled.…”
Section: Cholinergic Dysfunction and Epileptic Activity In The Tempormentioning
confidence: 99%
“…This process has been shown to be long lasting and associated with enhanced sensitivity to AChE inhibitors and muscarinic antagonists (Meshorer et al, 2002). Thus, it seems likely that muscarinic‐induced kindling is associated with such processes (Wasterlain and Jonec, 1983; Wasterlain et al, 1985).…”
Section: Cholinergic Dysfunction and Epileptic Activity In The Tempormentioning
confidence: 99%
“…This may be due to the cholinergic stimulation, which led to an imbalance between excitatory and inhibitory pathway and increase in glutamate levels which ultimately activated N-methyl-D-aspartate. [13,24,25] The normal GABA level in rat brain homogenate was reported as 1.49 ± 0.06 µmole/g brain wet weight. [23] Brain homogenate of kindled animals showed GABA levels lower than this level, and this effect can be attributed to kindling, in which there is selective lesion of GABA synthetic pathway.…”
Section: Discussionmentioning
confidence: 99%